Effects of subpressure on the sealing ability of dental sealant in vitro. (September 2018) - Tian, Y.M.; Zhuge, R.S.; Zhang, Z.T.; Zheng, D.X.; Ding, N.; Li, Y.M.
Abstract: Objectives: Pits and fissures sealing with flowable materials is a popular method for preventing caries in preventive dentistry while there is still microleakage existed. This in vitro study aimed to explore the effects of subpressure technique on the sealing ability of pit and fissure sealant. Materials and methods: One hundred and forty-one extracted human premolars were collected in this study and treated with different pressure (atmosphere pressure as group C, −0.04 MPa as group S4 and −0.08 MPa as group S8 ). Thermocycling (×5000) was also performed. Penetration percentage, microleakage, cross-sectional microhardness (Knoop, KMH) and mineral loss were evaluated. Kappa tests, Friedman nonparametric and two-way ANOVA were used for data analysis. Results: Penetration percentages of group S4 and S8 were significant higher compared to that of group C. Microleakage of groups was similar before thermocycling, while subpressure groups showed lower scale of microleakage after thermocycling. Data of KMH and mineral loss showed significant differences between subpressure and thermocycling groups. Significance: Subpressure technique could increase the penetration of pit and fissure sealant, decrease microleakage and increase resistance of demineralization after thermocycling. This novel technique may have great potential for preventing from secondary caries. Graphical abstract: Subpressure technique could increase the filled area of sealant in pits and fissures, decrease microleakage and increase resistance of demineralization after thermocycling. This novel technique may have great potential for preventing from secondary caries. fx1